1981
DOI: 10.1302/0301-620x.63b3.7263743
|View full text |Cite
|
Sign up to set email alerts
|

Partial undercutting facetectomy for bony entrapment of the lumbar nerve root

Abstract: Seventy-eight patients who had been operated on for bony entrapment of lumbar nerve roots were studied in an attempt to define the clinical syndrome, and to assess the results of a new technique of decompression which preserves spinal stability. The mean age of the patients was 45 years and 28 of them had previously undergone spinal operations. Pain in the leg was the predominant symptom, with evidence of motor involvement in half of the patients. Signs of nerve root tension were found in only one-third of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…Surgical procedures aim to decompress the nerve root emerging from the thecal sac along its course in the lateral recess. A multitude of surgical procedures for surgical decompression of symptomatic lateral recess stenosis have been described ranging from standard open laminectomies to minimally invasive decompressive techniques (14)(15)(16)(17)(18)(19)(20)(21)(22). In the current study we describe the surgical technique of endoscopic interlaminar lateral recess decompression in a small cohort of patients with unilateral symptomatic lateral recess stenosis with well-defined radiographic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical procedures aim to decompress the nerve root emerging from the thecal sac along its course in the lateral recess. A multitude of surgical procedures for surgical decompression of symptomatic lateral recess stenosis have been described ranging from standard open laminectomies to minimally invasive decompressive techniques (14)(15)(16)(17)(18)(19)(20)(21)(22). In the current study we describe the surgical technique of endoscopic interlaminar lateral recess decompression in a small cohort of patients with unilateral symptomatic lateral recess stenosis with well-defined radiographic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…In the Framingham population study, 19-47% of Americans 60 years and older were found to have radiographic evidence of spinal stenosis depending which radiographic criteria were used (1). A multitude of surgical procedures for decompression of lateral recess stenosis have been described ranging from standard open laminectomies to minimally invasive decompressive techniques (2)(3)(4)(5)(6)(7)(8). The goal of these procedures for treating patients experiencing lumbar radicular symptoms secondary to degenerative foraminal narrowing is to expand the stenotic neural foramen relieving the compressed traversing nerve root.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable disadvantages, such as increased time of surgery and hemorrhage, increased risk of nerve injury by pedicle screws, or postoperative loosening of rigid implants in osteoporotic bone, are connected to this technique. By using the more anatomical, atraumatic, and physiological technique of "undercutting laminectomy", an effective decompression of the spinal canal can be performed while leaving the posterior elements essentially intact [5,6,8,12,29,36]. If fusion is considered necessary, translaminar screws offer an option of fixation with the technique of "undercutting laminectomy" without considerable risk or lengthening of the operation time.…”
Section: Lumbar Spinal Stenosismentioning
confidence: 99%